Analisis dan Perancangan Sistem Informasi Akuntansi Pelaporan Keuangan Penjualan Susu pada Koperasi Unit Desa Sarwa Mukti - Shifa Sulastiani; Muhammad Anggionaldi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
KUD Sarwa Mukti is a dairy cooperative in Cisarua District, West Bandung Regency, which to this day still records milk sales transactions, and receivables manually, without integration across its business units. This condition makes the cooperative prone to recording errors, data duplication, reporting delays, and weak internal control. This study aims to analyze the current accounting information system for financial reporting on milk sales and to design an integrated, website-based system. Weaknesses in the existing system were analyzed using the PIECES method, while the system design followed the Waterfall approach,. Data were collected through observation, interviews, and documentation studies. The research resulted in a system design called DIGIKOP, built on PHP and MySQL which includes modules for sales transactions, payments, journals, general ledgers, and automated financial reports. The proposed system is expected to speed up recording, improve data accuracy, strengthen internal control, and enhance the transparency of financial reporting at KUD Sarwa Mukti.